ESTUFAS, TELADOS E SUBSTRATOS NO CRESCIMENTO DE MUDAS DE AMOR – PERFEITO (Viola tricolor L.) - VIEIRA, Mariane Tavares; SOUZA, Larissa Gabriela Pereira; MARQUES, Ana Letícia Ribeiro; COSTA, Edilson2 (edilson.costa@uems.br);; DUARTE, Ítala Layane (ANAIS DO ENIC, 2023)
-